Do institutional investors play hide-and-sell in the IPO aftermarket? - Nefedova, Tamara; Pratobevera, Giuseppe (Journal of Corporate Finance, 2020)
We document a robust buy/sell asymmetry in the choice of the broker in the IPO aftermarket: institutions that sell IPO shares through non‑lead brokers tend to have bought them through the lead underwriters in the IPO aftermarket. This trading behavior is consistent with institutional investors hiding their sell trades and presumably breaking their laddering agreements with the lead underwriters. The asymmetry is the strongest in cold IPOs and is limited exclusively to the first month after the issue, when the incentives not to be detected are the strongest. We show that the intention to flip IPO allocations is not an important motive for hiding sell trades from the lead underwriters. We find that hiding sell trades is an effective strategy to circumvent underwriters' monitoring mechanisms: the more institutions hide their sell trades, the less they are penalized in subsequent IPO allocations.